Improving the thermal conductivity of epoxy resin by the addition of a mixture of graphite nanoplatelets and silicon carbide microparticles - T. Zhou; X. Wang; P. Cheng; T. Wang; D. Xiong; X. Wang (eXPRESS Polymer Letters)
In this work, an alternative type of carbon-based nanofiller, graphite nanoplatelets (GNPs) with comparable properties, easier and lower-cost production, were used to improve the thermal conductivity of an epoxy. By adding 12 wt% GNPs or 71.7 wt% silicon carbide microparticles (micro-SiCs) to epoxy, the thermal conductivity reached maxima that were respectively 6.3 and 20.7 times that of the epoxy alone. To further improve the thermal conductivity a mixture of the two fillers was utilized. The utilized GNPs are characterized by two-dimensional (2-D) structure with high aspect ratio (~ 447), which enables GNPs effectively act as heat conductive bridges among 3-D micro-SiCs, thus contributes considerably to the formation of a more efficient 3-D percolating network for heat flow, resulting in higher thermal conductivity with relatively lower filler contents which is important for decreasing the density, viscosity and improving the processability of composites. A thermal conductivity, 26.1 times that of epoxy, was obtained with 7 wt% GNPs + 53 wt% micro-SiCs, thus not only break the bottleneck of further improving the thermal conductivity of epoxy composites but also broaden the applications of GNPs.